The Effect Of Noticing Technique Toward Teaching Simple Present Tense And Simple Past Tense At The First Grade At The First Grade In SMPN 3 Sungai Pua - Nova Melia Ramadani; Absharini Kardena; Genta Sakti; Merry Prima Dewi; Imelia Nova (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This research was due to by several problems of students’ in the first grade in SMP N 3 Sungai Pua related to students’ achievement in English learning especially in lesson simple present tense and simple past tense. This research to determine whether there was a significant effect and whether there was significant difference using the Noticing technique on students’ achievement in lesson simple present tense and simple past tense and to determine whether students’ achievement using the noticing technique was the best than not using the noticing technique. This study was classified as a quasi-Experiment design. There was experimental group, namely the VII.B class (19 students’) and the control group namely VII.A (20 students’). Data obtained through pre-test and post-test . Pre- test was given to both groups before treatment and post-test was given after treatment.Treatment using the noticing technique was only given to the experimental group. After the data was collected, the researcher analyzed the data with a significant of α = 0,05. From the results of statistical analysis, the first hypothesis was obtained; there was a significant effect using the noticing technique on students' achievement in simple present tense and simple past tense lesson. The analyzes of the data showed that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted because tobtained (26,46) was higher than ttable (20,93) with the level significant α of 0,05. The second hypothesis there was a significant difference using noticing technique on teaching simple present tense and simple past tense. The analyzes of the data showed that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted because tobtained (50,13) was higher than ttable (20,86) with the level significant of α 0.05. Finally, the third hypothesis that teaching simple present tense and simple past tense for the students who were taught by using noticing technique better than the students who were taught conventional method toward student’s achievement . The analyzes of the data showed that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted because tobtained (50,13) was higher than ttable (20,86) with the significant of α 0,05. In this manner, it may well be conclude that the noticing technique seem influenced for understandies accomplishment in learning simple present tense and simple past tense to be way better than without utilizing the taking noticing technique.